2011
DOI: 10.1145/1952982.1952995
|View full text |Cite
|
Sign up to set email alerts
|

False data injection attacks against state estimation in electric power grids

Abstract: A power grid is a complex system connecting electric power generators to consumers through power transmission and distribution networks across a large geographical area. System monitoring is necessary to ensure the reliable operation of power grids, and state estimation is used in system monitoring to best estimate the power grid state through analysis of meter measurements and power system models. Various techniques have been developed to detect and identify bad measurements, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1,072
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,957 publications
(1,128 citation statements)
references
References 22 publications
1
1,072
0
2
Order By: Relevance
“…The majority of this research proposes defending attacks at the network or process level. The basis for the attack model used for the physical experiment described in Section 8 was the FDI concept introduced in [21]. One form of FDI attack known as a replay attack [22] shows that attackers can mislead traditional fault detectors while still providing arbitrary input to controllers.…”
Section: Related Workmentioning
confidence: 99%
“…The majority of this research proposes defending attacks at the network or process level. The basis for the attack model used for the physical experiment described in Section 8 was the FDI concept introduced in [21]. One form of FDI attack known as a replay attack [22] shows that attackers can mislead traditional fault detectors while still providing arbitrary input to controllers.…”
Section: Related Workmentioning
confidence: 99%
“…It is worth to mention that both power grids and buildings have been prone to cyber-attack even before their interconnection in the form of the internet of things. However, due to the increased points of entries in a heterogeneous network with interconnected devices and their different capabilities, and because of distributed, multi-agent control system in contrast with the hierarchical control system in conventional networks, it is complicated to provide a strong and uniform protection for the entire smart network [9] [11]. Figure 2 provides a comparison between conventional and smart methods of energy metering.…”
Section: Smart Grid Vulnerabilitymentioning
confidence: 99%
“…Unfortunately, this detection approach cannot ensure the integrity of the data transmitted to the control center. It has been shown in [1] that a wise attacker can construct the coordinated false data z "H∆θ to avoid being detected by the residual checking. Thus, such an attack is called undetectable false data injection attack.…”
Section: Review Of False Data Injection Attacksmentioning
confidence: 99%
“…Consequently, SCADA systems are becoming the primary target of cyber-attacks. It has been shown that an attacker can compromise the Direct Current (DC) state estimation by launching false data injection attacks, which could be undetectable if the attacker can construct the false data that obeys Kirchhoff's Current Law (KCL) and Kirchhoff's Voltage Law (KVL) based on the full network information of the power grid [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation